1995
DOI: 10.1016/s0741-5214(95)70297-0
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic aneurysm of the intrathoracic subclavian artery: A case report and review of the literature

Abstract: True aneurysm of the subclavian artery is extremely rare. Excluding the more common aneurysms of an aberrant right subclavian artery, those associated with thoracic outlet syndrome, and posttraumatic "aneurysms," atherosclerosis is the most common cause. Syphilis, tuberculosis, and cystic medial necrosis are less often the cause. These aneurysms can rupture, thrombose, embolize, or cause symptoms by local compression. Surgical treatment is generally indicated, and has evolved from ligation procedures to extirp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
1
12

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 24 publications
1
78
1
12
Order By: Relevance
“…[1,2] In a literature review, Hobson et al [13] identified 195 cases of aneurysms and found only 1% of all peripheral aneurysms originated from the subclavian artery. The aneurysms can be classified in terms of location on the subclavian artery, as extrathoracic and intrathoracic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] In a literature review, Hobson et al [13] identified 195 cases of aneurysms and found only 1% of all peripheral aneurysms originated from the subclavian artery. The aneurysms can be classified in terms of location on the subclavian artery, as extrathoracic and intrathoracic.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,6] Elective surgical repair is the treatment of choice for most subclavian aneurysms, as they have an increased risk of rupture, embolization, thrombosis, and other complications. [1,7,9] Surgical approach for aneurysms of the left subclavian artery, a left-side lateral thoracotomy is used, for aneurysms on the right subclavian, are best approached by median sternotomy, improved control of the ascending aorta and the aneurysm's neck can be achieved with sternotomy with or without a supraclavicular incision and the sternoclavicular joint may or may not be disarticulated. [4,10] The resection of the aneurysm is preferred to simple ligation, as continued growth and rupture of ligated aneurysms have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Other authors described patency rates between 80 and 100%. 4,5,[9][10][11][12][13][15][16][17] Another application of the endovascular treatment documented in the literature was to exclude an iatrogenic pseudoaneurysm of the subclavian artery. 18,19 Schoder et al described a series of 12 patients submitted to endovascular treatment with implantation of a covered stent for aneurysmal disease and subclavian artery trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Rüp-tür, tromboz gelişimi, periferal emboli ve üst ekstremitelerde iskemi başlıca komplikasyonlardır (5,6). Akciğer grafisi, arteriografi, bilgisayarlı tomografi ve anjiografi tanıda kullanılan başlıca yöntemlerdir (2). Tedavide ana yöntem cerrahidir.…”
Section: Abstract: Trauma Gunshot Injury Subclavian Artery Endostunclassified